REI: riparian ecosystem index to assess the impact of hydrologic regime changes on riparian ecosystems. Issue 1 (20th March 2015) - Benjankar, Rohan; Yager, Elowyn; Tonina, Daniele; Merz, Norm
Abstract: We developed a geographic information systems (GIS)‐based multi‐metric assessment tool using model‐simulated long‐term vegetation data to assess changes in riparian ecosystems due to altered hydrologic regimes. This allowed us to estimate spatial changes in a riparian system over several decades at annual resolution, to study system trends through time, and the effect of multiple and time‐distributed human activities. We applied the tool to assess human and hydrologic impacts, for two scenarios, pre‐dam versus post‐dam periods and pre‐levee versus post‐levee periods on the Kootenai River. The pre‐dam versus post‐dam scenario considers two distinct hydrologic regimes as a result of dam operation, whereas the pre‐levee versus post‐levee scenario has one single natural hydrologic regime. We compared riparian ecosystem, community composition and native woody riparian vegetation index scores within the two scenarios. Our results showed that all three time‐averaged index scores (riparian ecosystem, community composition and native woody vegetation) were statistically higher for the pre‐dam than the post‐dam period. In contrast, differences in index scores were small and were not statistically significant between pre‐levee and post‐levee periods. Thus, our GIS‐based assessment tool can detect the impact of human‐induced changes in the natural hydrologic regime on riparian ecosystems both temporally and spatially. Copyright © 2015 John Wiley & Sons, Ltd.